1ISG-033 Inflammatory bowel disease: biological prescribing trends in an italian hospital. (March 2019) - Inserra, C; Zovi, A; Vimercati, S; Piacenza, M; Zerega, G
Abstract : Background: Inflammatory bowel disease (IBD) is a group of inflammatory conditions of the colon and small intestine. The major types of IBD are ulcerative colitis and Chron's disease. Symptoms can occur at any time and exacerbations can be followed by periods of remission. The objective of IBD treatment is induction, maintenance of remission or both. An increasing number of biologics have been approved for the treatment of refractory moderate to severe IBD in patients who have not responded to traditional therapy, but due to the absence of direct comparison data and the introduction of biosimilars, treatment choice is still controversial. Purpose: The aim of this study is to analyse prescribing trends of biologics used at the centre for the treatment of patients with moderate to severe IBD refractory to traditional therapy. Material and methods: Data were extracted from the management software used at the centre and collected in an Excel spreadsheet. Included data were: dispensing data of biologics prescribed for every refractory moderate to severe patient with IBD treated at the centre between January 2014 and November 2017. For each patient dispensed treatments, switches and reason for switches were analysed. Results: Eight-hundred and fourteen patients with IBD treated with biologics were included: Adalimumab (42.7%), Infliximab (27.4% originator; 14.4% biosimilar), Golimumab (6.8%) and Vedolizumab (8.7%). Five per cent of overall in-treatment patients changed treatment. Switch rates were: 8.5% from Infliximab originator to Vedolizumab, 3.6% from Golimumab to Adalimumab, 1.8% from Golimumab to Infliximab biosimilar, 12.8% from Infliximab biosimilar to Vedolizumab, 2.8% from Vedolizumab to Infliximab biosimilar, 4.5% from Infliximab originator to Infliximab biosimilar and 1.7% from Infliximab biosimilar to originator. Reasons for switching were inefficacy (61%) or treatment cost reduction (39%). Conclusion: Analysis showed a high variability in biological therapy prescription trends at the centre, which could be related to patients' characteristics. Even in the absence of clear comparison data between different treatments, clinical choices included all biological treatments approved in Italy, which were almost always effective and were associated with a low overall switch rate. References and/or acknowledgements: No conflict of interest.